Graphene crystal growth by thermal precipitation of focused ion beam induced deposition of carbon precursor via patterned-iron thin layers - Rius, Gemma; Perez-Murano, Francesc; Yoshimura, Masamichi (Nanofabrication, 2014)
Recently, relevant advances on graphene as a building block of integrated circuits (ICs) have been demonstrated. Graphene growth and device fabrication related processing has been steadily and intensively powered due to commercial interest; however, there are many challenges associated with the incorporation of graphene into commercial applications which includes challenges associated with the synthesis of this material. Specifically, the controlled deposition of single layer large single crystal graphene on arbitrary supports, is particularly challenging. Previously, we have reported the first demonstration of the transformation of focused ion beam induced deposition of carbon (FIBID-C) into patterned graphitic layers by metal-assisted thermal treatment (Ni foils). In this present work, we continue exploiting the FIBID-C approach as a route for graphene deposition. Here, thin patterned Fe layers are used for the catalysis of graphenization and graphitization. We demonstrate the formation of high quality single and few layer graphene, which evidences, the possibility of using Fe as a catalyst for graphene deposition. The mechanism is understood as the minute precipitation of atomic carbon after supersaturation of some iron carbides formed under a high temperature treatment. As a consequence of the complete wetting of FIBID-C and patterned Fe layers, which enable graphene growth, the as-deposited patterns do not preserve their original shape after the thermal treatment.